Metodología Basada en Proceso de Jerarquía Analítica (AHP) para Seleccionar Cadenas Productivas que Buscan Soluciones de Automatización a Bajo Costo - Gómez Montoya, Diego; Méndez Giraldo, Germán Andrés; Méndez Morales, Edgar; Ortiz Chavarro, Giovanny; Turriago Hoyos, Álvaro (Ingeniería, 2007)
This paper presents the methodology used in order to identify and select three production chains, based in a set of 20 possible chains (17 of them so called "Priority" and the rest of them called "promissory Chains"). The document is framed into the project called "By means of Competitive Intelligence methodologies and asociativeness schemas, to develop a supply in assets and services of low cost automation which satisfy the requirements of modernization on three productive chains, potentially clients of the Electro Electronic Industry Cluster of Bogotá and Cundinamarca"; the project has been financed by Colciencias and developed by CIDEI (Center of Investigation and Technological Development of the Electro Electronic and Informatics Industr y, for his Spanish abbreviation) and the Cundinamarca University. These chains will be boarded in the close future in order to select companies in which will be made a process destined to generate low cost automation solutions whose will generate highest productivity levels. The set of variables that served like as criteria for the selection was defined by the group of researchers and to determine the relative importance of each criterion in the weighted average was used the Analytical Hierarchy Process or AHP, by using the qualifications assigned in several rounds on the part of a group formed by experts, researchers and industrialists of the Electronic sector. Having the relative weight of each criterion, those will be described as qualitative or quantitative form, by their nature and according to researchers' scale, presenting the priority order in which the chains had to be boarded according to the defined criteria to fulfill the project objective. At the end of the investigation, the productive chains of Foods with added value, Textiles and Dressmaking and Flowers were elected.